Перелом: опыт прочтения несекретных документов / О. Р. Лацис - Лацис Отто Рудольфович (Политиздат, 1990)
Экземпляры: КХ (20100430) / Инвентарный номер: 964134 / Цена: 1.60 / Сис.шифр: 66.61(2)8 / Авт.знак: Л 30 / ГРНТИ: 03 / ББК: 63.3(2)6-8